Xanthorrhizol Induces Apoptosis Via the Up-regulation of Bax and p53 in HeLa Cells - Ismail, Norzila; Pihie, Azimahtol Hawariah Lope; Nallapan, Meenakshii (International Institute of Anticancer Research (IIAR), 2005)
Xanthorrhizol is a sesquiterpenoid compound extracted from Curcuma xanthorrhiza, which is known locally as Temulawak. Traditionally, C. xanthorrhiza was found to have antibacterial, anticancer and anti-inflammatory activity. The rhizome has also been used to treat inflammation in postpartum uterine bleeding. An antiproliferative assay using methylene blue staining revealed that xanthorrhizol inhibited the proliferation of the cervical cancer cell line HeLa with an EC50 value of 6.16 Ìg/ml. Xanthorrhizol significantly increased apoptosis in HeLa cells, as evaluated by the Tdt-mediated dUTP nick end-labelling (TUNEL) assay and nuclear morphology by Hoechst 33258 staining. Western blot analysis, which was further confirmed by the immunostaining results, implied an up-regulation of tumor suppressor protein p53 and the pro-apoptotic protein Bax, following the treatment with xanthorrhizol. Xanthorrhizol, however, did not affect the expression of the anti-apoptotic protein, Bcl-2 and the viral oncoprotein, E6. Hence, xanthorrhizol is a promising antiproliferative and anticancer agent which induces p53 and Bax-dependent apoptosis in HeLa cervical cancer cells